Spatial Variability of Soil Nutrients Content Related to Rice Yield - Tamaluddin Syam (UNIVERSITY OF LAMPUNG, 2010)
Spatial Variability of Soil Nutrients Content Related to Rice Yield (T Syam): Soil nutrients content and its spatial distribution are very important data for site specific fertilizer management to supply sufficient crop nutrition. The study was carried out at the farmer paddy field in Rejomulyo Village, Metro Town District of Lampung Province. The aim of this study was to evaluate the relationship between soil nutrients content (N, P, K) and rice yield. Soil samples were collected before fertilizers treatment by the grid sampling method and GPS was used as a tool for precisely determine sample site location. Rice yield data were collected by small plot method on the each-of soil sample location. Spatial analysis using GS + software and statistical analysis using SPSS software. The result indicated that total nitrogen in the soil had a significantly correlation with the rice yield (r = 0.95**) and their spatial distribution was relatively similar each others. Spatial maps of soil nutrients content could be used for the variable rate fertilizers treatment, especially for nitrogen.